Comparative study of the bioaccessibility of the colorless carotenoids phytoene and phytofluene in powders and pulps of tomato: microstructural analysis and effect of addition of sunflower oil. Issue 9 (7th September 2018) - Mapelli-Brahm, Paula; Stinco, Carla M.; Meléndez-Martínez, Antonio J.
Abstract : The bioaccessibility of phytoene and phytofluene, two carotenoids that are attracting much attention, from tomato powders and pulps was analysed. Abstract : The objective was to assess the potential bioavailability of phytoene (PT) and phytofluene (PTF) from tomato powders used as raw materials for supplements as compared to the pulp of a common tomato and a cherry tomato. PT and PTF are attracting much interest nowadays as they can provide health and cosmetic benefits. PT and PTF levels in the more concentrated powder were up to 1000 times higher than in the tomatoes. The bioaccessibility from the powders was lower as compared to the tomato fruits and increased markedly when sunflower oil was added. However, the best source of potentially absorbable PT and PTF (0.5 and 2 mg g −1 respectively) was by far the powder with higher levels of them. This result could be due to the higher carotenoid concentration in the powder, the reduction of the particle sizes, and the rupture of cell structures compared to the pulps.